(untitled) (Research, Society and Development, 2020)
In this work we collect data and analyze content related to public policies of Distance Learning in Brazil. We use exploratory and explanatory literature review studies, relevant to public policies on distance education, and the selection of these databases was based on their indexing studies on distance education and educational public policies. We note that, although there are several positive initiatives in public policies, there is also a huge lack of infrastructure, planning and management investments for their realization. In addition, there is little integration involved in the process, which hinders better development, further confirming that this teaching modality is not always fully included in the institutional priorities to which it belongs. In terms of the execution of these public policies we also verified that the planning needs a better alignment in relation to the demands of the market and the target public, which demands greater competence of the managers in the processes, seeking to make them more qualitative in all aspects. In summary, we can consider that reflecting and discussing public policies, their implementation and their effectiveness in DE represent a critical analysis of integrative factors between the parties involved, seeking to provide a contribution of permanent adjustments in the contents and strategies of this important educational modality.